"Her bun in my oven": Motivations and experiences of two‐mother families who have used reciprocal IVF. Issue 1 (2nd December 2022) - Shaw, Kate; Bower‐Brown, Susie; McConnachie, Anja; Jadva, Vasanti; Ahuja, Kamal; Macklon, Nick; Golombok, Susan
Abstract: Objectives: What motivates same‐gender female couples to choose reciprocal in vitro fertilization (IVF)? Do their experiences of becoming and being a mother via reciprocal IVF match their pre‐parenthood expectations? Background: Reciprocal IVF is a treatment route available to cis, same‐gender female couples, and other couples in which both partners have a uterus and egg stores. One partner's egg is retrieved, fertilized in vitro with donor sperm, then carried by the other partner. Existing debate has considered the ethical implications of this treatment route. To date, no empirical research has explored the experiences of families who have used reciprocal IVF. Method: Semistructured interviews were conducted with genetic and gestational mothers in 14 families headed by cis, same gender female couples who had conceived by reciprocal IVF in the United Kingdom ( N  = 28 mothers). Data were analyzed according to the principles of reflexive thematic analysis. Results: Four themes were constructed: (a) becoming mums together; (b) legitimacy: "who's the real mum"; (c) choices and constraints; and (d) biological connections strengthen family connections. Conclusion: Families had multiple and nuanced motivations for choosing reciprocal IVF, such as the desire to share the journey of motherhood with their partner, to be perceived as legitimate parents, to overcome practical barriers, and to build strong family relationships. Mothers' pre‐parenthood expectations often mismatched the reality of becoming and being a mother via reciprocal IVF. Most parents found that the significance of reciprocal IVF diminished as their children grew up. Implications: Findings demonstrate that reciprocal IVF offers a fulfilling route to parenthood. Parents should have access to routes to parenthood that meet their reproductive needs and feel right for them as a couple.